English Language Education Students' Use of the Duolingo App in English Learning - Renova, Hanindya Ichthy; Kurniawan, Fitri (Universitas Pahlawan Tuanku Tambusai, 2025)
This descriptive qualitative study investigates English Language Education students' perceptions of the Duolingo app, focusing on its perceived disadvantages. The subjects were students from the English Language Education Study Program at Muhammadiyah University of Surakarta. The findings indicate that students generally view Duolingo positively, citing its user-friendly design, gamified elements, and interactive learning techniques as key strengths. Features like badges, levels, and game-based exercises effectively maintain motivation and engagement in language learning.